Opening Cinematics: Their Cost-Effectiveness in Serious Games. (February 2014) - Procci, Katelyn; Lakhmani, Shan; Hussain, Talib S.; Bowers, Clint A.
For the development of serious gaming, it is necessary to articulate the specific features that lend themselves best to the creation of effective learning games. Given the limited resources of the typical serious games developer, time and money should be spent in a way such that features with the greatest return on investment take priority. Opening cinematics, a popular feature of games, was examined through the lens of three major theoretical perspectives that promote learning, specifically situated learning, emotional arousal, and goal orientation. A series of three experiments was conducted to determine if the inclusion of opening cinematics was able to change the goal orientation of players as well as improve the effectiveness of a serious game used to train U.S. Navy recruits shipboard damage control procedures. The data suggest that opening cinematics were not worth the immense development investment. Game design suggestions and potential topics for future research are provided.